Unramified nonspecial real space curves having many real branches and few ovals - Huisman, J. (Revista Matemática Complutense, 2002)
Let C _ Pn be an unramified nonspecial real space curve having many real branches and few ovals. We show that C is a rational normal curve if n is even, and that C is an M-curve having no ovals if n is odd.